Separation, Purification, and Characterization of Sterol Fatty Acid Esters From Lotus Plumule. Issue 12 (9th October 2017) - Chen, Shuai; Bi, Yanlan; Chen, Jiali; Wei, Maolin; Sun, Shangde; Chen, Jingnan
Abstract : In this work, a new plant resource (lotus plumule) is used to produce sterol fatty acid ester (SFAE). Acetone extraction and column chromatography are developed for the separation and purification of SFAE. Silica gel (200–300 mesh) was the best adsorbent according to the static and dynamic adsorption experiments. The adsorption of SFAE on silica gel (200–300 mesh) is well fitted to Langmuir isotherm model. The column chromatography conditions (elution solvents, loading amount, column height to diameter ratio, and elution flow rate) are optimized and the purity and recovery yield of SFAE are up to 95.56 ± 1.32% and 95.70 ± 3.05%, respectively. Purification processes have no significant effect on sterol composition and fatty acid composition of SFAE. Moreover, SFAE products are identified by UV and IR spectra using standard sample, as well as GC‐MS. GC results show that, β ‐sitosterol (49.6%), △5‐avenasterol (33.4%), and campesterol (9.1%) are the main sterols; and linoleic acid (63.1%), behenic acid (8.3%), and oleic acid (8.1%) are the main fatty acids. Practical Applications : This work provides an economic and efficient method for high purity SFAE production, which gave some available information for the value‐added utilization of idle plant materials with high levels of SFAE. A new plant resource, lotus plumule, is used to produce sterol fatty acid ester (SFAE). Acetone extraction and column chromatography are developed for separation and purification of SFAE. The SFAE product is a pale yellow oily liquid with high purity (95.6%) and recovery (95.7%), which is analyzed and confirmed by GC, MS, and ultraviolet and infrared spectroscopy. Abstract : A new plant resource, lotus plumule, is used to produce sterol fatty acid ester (SFAE). Acetone extraction and column chromatography are developed for separation and purification of SFAE. The SFAE product is a pale yellow oily liquid with high purity (95.6%) and recovery (95.7%), which is analyzed and confirmed by GC, MS, and ultraviolet and infrared spectroscopy.